2008
DOI: 10.1007/s10585-008-9157-3
|View full text |Cite
|
Sign up to set email alerts
|

Decreased adhesiveness, resistance to anoikis and suppression of GRP94 are integral to the survival of circulating tumor cells in prostate cancer

Abstract: The presence of circulating tumor cells (CTC) is common in prostate cancer patients, however until recently their clinical significance was unknown. The CTC stage is essential for the formation of distant metastases, and their continuing presence after radical prostatectomy has been shown to predict recurrent or latent disease. Despite their mechanistic and prognostic importance, due both to their scarcity and difficulties in their isolation, little is known about the characteristics that enable their producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 48 publications
3
26
0
Order By: Relevance
“…This result conformed to the research conducted by Mao et al (2008). Howard et al (2008) investigated the molecular mechanism for the survival of CTCs, which was through downregulated adhesive molecules, resistance to anoikis, and low GPR94 expression.…”
Section: Molecular and Genetic Characterization Of Ctcssupporting
confidence: 86%
“…This result conformed to the research conducted by Mao et al (2008). Howard et al (2008) investigated the molecular mechanism for the survival of CTCs, which was through downregulated adhesive molecules, resistance to anoikis, and low GPR94 expression.…”
Section: Molecular and Genetic Characterization Of Ctcssupporting
confidence: 86%
“…Mouse CTCs were obtained from the blood specimens of the animals by cardiac puncturing as described previously (25). Nucleated cells from mouse blood were enriched in erythrocytes lysis buffer, and the epithelial cells were isolated by magnetic antibody cell separation (Miltenyi Biotec) and resuspended in 0.1 ml of PEB (1ϫ PBS, 0.1 mM EDTA, and 0.5% BSA fraction V) (Sigma) as described previously.…”
Section: Methodsmentioning
confidence: 99%
“…Except for certain cell types such as blood cells, most cells are inter-connected via cell-cell and cell-extracellular matrix adhesions [2], and it is commonly observed that those cells develop apoptotic and necrotic signatures when placed under detached conditions [3, 4]. The deregulation of anoikis is emerging as a hallmark of cancer [5], and resistance to anoikis stress is one of the critical aspects for cancer stem cells [6] and circulating tumor cells (CTCs) [7]. Epithelial-mesenchymal transition was proposed as one of the mechanism underlying the acquisition of anoikis resistance of cancer cells [8].…”
Section: Introductionmentioning
confidence: 99%